(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
It is considered a complication of cholelithiasis with duodenal cholecyst fistula and rarely colonic cholecyst. It occurs when there is a bile-enteric fistula as a consequence of recurrent acute cholecystitis where the gallbladder adheres to the duodenum or colon, causing necrosis and perforation of these two organs that are in contact. Gallstone ileus is a condition of elderly patients and therefore often with comorbidity factors, which is why the immediate resolution of the obstructive condition is the best way to reduce the rate of complications in these patients, that is, early resolution. The case of a male patient, 68 years old, diabetic, who presented with abdominal pain, nausea, vomiting, and intermittent abdominal distension, was presented topographically as gallstone ileus due to the presence of an intraluminal stone in the ileus whose surgical resolution was in a single stage.